Confirmatory Factor Analysis of the Antisocial Process Screening Device - Pechorro, Pedro (2016)
The main aim of the present study was to examine the factor structure, internal consistency, and some additional psychometric properties of the Antisocial Process Screening Device-Self-Report (APSD-SR) among a large forensic sample of incarcerated male juvenile offenders ( N = 438). The results, based on this forensic sample, support the use of the APSD-SR in terms of its factor structure, and internal consistency despite the fact an item had to be removed from the callous-unemotional (CU) dimension. Statistically significant positive associations were found with measures of psychopathic traits, CU traits, narcissism, and aggression, as well as negative associations with a measure of empathy. Findings provide support for the use of the APSD-SR among the incarcerated male juvenile offender population.